IMPLEMENTASI MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI KELAS V DI SDN GLUNDENGAN 01 TAHUN 2025/2026 - Umi Rosyidah; Dwi Juli Priyono (Tarbawi, 2026)
This study aims to improve students’ learning outcomes in Islamic Religious Education and Character Education through the implementation of the Talking Stick learning model in fifth-grade students of SDN Glundengan 01. The method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects were 30 students. Data collection techniques included learning outcome tests, observation of student activities, and documentation. The results of the study indicate a gradual improvement in learning outcomes. In the pre-cycle stage, the average student score was 68 with a learning completeness rate of 40%. In Cycle I, the average score increased to 74 with classical completeness reaching 60%. Furthermore, in Cycle II, a significant improvement occurred, with the average score reaching 90 and learning completeness achieving 100%. The minimum student scores also increased at each stage, indicating a more even distribution of learning outcomes. Thus, the implementation of the Talking Stick model has proven effective in improving students’ learning outcomes. In addition, this model creates a more active, interactive, and enjoyable learning environment, encouraging greater student involvement in the learning process.